Long-term evaluation of eyes with central corneal thickness <400 µm following laser in situ keratomileusis - Djodeyre MR (Dove Medical Press, 2016)
Mohammad Reza Djodeyre,1 Jaime Beltran,2 Julio Ortega-Usobiaga,3 Felix Gonzalez-Lopez,4 Ana Isabel Ruiz-Rizaldos,1 Julio Baviera2 1Department of Refractive Surgery, Clinica Baviera, Zaragoza, 2Department of Refractive Surgery, Clinica Baviera, Valencia, 3Department of Research and Development, Clinica Baviera, Bilbao, 4Department of Refractive Surgery, Clinica Baviera, Madrid, Spain Purpose: To study long-term refractive and visual outcomes of laser in situ keratomileusis (LASIK) in eyes with a postoperative thin central cornea.  Methods: In this retrospective observational case series, we studied 282 myopic eyes with a normal preoperative topographic pattern and postoperative thin corneas (<400 µm) that had at least 3 years of follow-up after LASIK in three private clinics. The main outcome measures were safety, efficacy, predictability, percent tissue altered, and complications.  Results: The mean postoperative central corneal thickness was 392.05 µm (range: 363.00–399.00 µm). After a mean follow-up of 6.89±2.35 years (standard deviation), the safety index was 1.17, the efficacy index was 0.94, and predictability (±1.00 diopter [D]) was 73.49. The mean residual stromal bed thickness was 317.34±13.75 µm (range: 275–356 µm), the mean flap thickness was 74.76±13.57 µm (range: 55–124 µm), and the mean percent tissue altered was 37.12%±3.62% (range: 27.25%–49.26%). No major complications were recorded.  Conclusion: LASIK with a resultant central cornea thickness <400 µm seems to be effective, safe, and predictable provided that preoperative topography is normal and the residual stromal bed thickness is >275 µm. Keywords: LASIK, thin, cornea, ectasia, myopia, pachymetry, topography